Vitamin D Deficiency Presenting as Proximal Myopathy: An Overlooked Diagnosis - A Case Series and Review of the Literature - Venkatraman Rajkumar (European Medical Journal)
The prevalence of vitamin D deficiency is ubiquitous. Severe disease can present very dramatically and can be misleading to the treating physician, resulting in mismanagement. A high index of suspicion in vulnerable patients should help circumvent this problem, including a thorough history and physical examination to lead the clinician in the right direction. Insidious onset and progressive proximal pelvic girdle myopathy, in the absence of other neurological findings, in the appropriate patient should prompt the physician to test for serum 25 hydroxyvitamin D levels. The literature on endocrine myopathy does not highlight this condition as much as it does the thyroid, parathyroid, and adrenal aetiologies. Testing for vitamin D deficiency is simple, and treatment is available all over the world. The following article presents three patients, in different scenarios, with the condition. In all three patients, incapacitating pelvic girdle weakness resolved and quality of life improved dramatically with timely intervention. Most importantly, the correct approach prevented misdiagnosis and mismanagement.